The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/jvi.00555-16
|View full text |Cite
|
Sign up to set email alerts
|

Generating Bona Fide Mammalian Prions with Internal Deletions

Abstract: Mammalian prions are PrP proteins with altered structures causing transmissible fatal neurodegenerative diseases. They are self-perpetuating through formation of beta-sheet-rich assemblies that seed conformational change of cellular PrP. Pathological PrP usually forms an insoluble protease-resistant core exhibiting beta-sheet structures but no more alpha-helical content, loosing the three alpha-helices contained in the correctly folded PrP. The lack of a high-resolution prion structure makes it difficult to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…All single amino acid variants except for recPrP T191P had melting temperatures around 70 °C, and recPrP T191A had the highest T m among this group (70.3 °C), consistent with the idea that the α-helix prone alanine stabilizes the helical structure of recPrP. Interestingly, recPrP T191P had the highest melting temperature (74.3 °C) among all recPrP variants, suggesting that this recPrP, with a shortened α-helix 2, is quite stable; this result is consistent with a recent report34. Importantly, there was no correlation between thermal stability and PrP conversion, either by PMCA or by amyloid fibril growth assay.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…All single amino acid variants except for recPrP T191P had melting temperatures around 70 °C, and recPrP T191A had the highest T m among this group (70.3 °C), consistent with the idea that the α-helix prone alanine stabilizes the helical structure of recPrP. Interestingly, recPrP T191P had the highest melting temperature (74.3 °C) among all recPrP variants, suggesting that this recPrP, with a shortened α-helix 2, is quite stable; this result is consistent with a recent report34. Importantly, there was no correlation between thermal stability and PrP conversion, either by PMCA or by amyloid fibril growth assay.…”
Section: Resultssupporting
confidence: 91%
“…1), and the role of this string in PrP conversion is controversial222425263334. In our PMCA study, all variants in this string had a reduced capability to form infectious prions, which could be due to the influence on three aspects of PrP conversion: (1) the seeding process, (2) the PrP conformational change, and (3) the final prion structure.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…20 We found that PrPD193-196 and PrPD193-197 conferred to RK13 cells the same degree of susceptibility to 127S infection than the wild-type protein. 17 The levels of PrP res accumulated in cells also compared at least up to 12 passages of the cultures. The size distribution of cell-formed PrP res aggregates was assessed by sedimentation velocity and found to be the same for the wild-type and mutant proteins (Fig.…”
Section: The C-terminus Of Prp Helix 2 Is Not Required For Prion Convmentioning
confidence: 99%
“…1) and found that removal of the last 5 residues of the helix H2 did not impair prion conversion. 17 This was the first clear-cut demonstration that a stretch of residues within the prion-associated domain of PrP is dispensable to generate bona fide prions.…”
mentioning
confidence: 99%